The Improvement of Critical Thinking Ability Students Through Inquiry Learning Model about Excretory System Class VIII in SMPN 11 Padang - MEZI YULIA ASTUTI; Heffi Alberida; Yosi Laila Rahmi (Bioeducation Journal, 2018)
Critical thinking is a purposeful and clear process used in mental activities such as problem solving, decision making, persuading, analyzing assumptions and conducting scientific research. The ability of thinking critically is effected by the competence of knowledge acquired by the students. Based on midterm exam, the result showed that 87,5% of students do not meet the minimum exhaustiveness criteria (KKM). One way that can be condusted to overcome it is applying inquiry learning model.the purpose of this research is to find out the effect of inquiry learning model towards studens’ critical thinking skills. The research is Quasi experiment research by using Randomized Control-Group Research Posttest Only Design. The population is VIII class student in SMPN 11 Padang. The sample is VIII.B students as an experiment class and VIII.C students as a control class, that are selected by purposive sampling technique. The instrument used is final test in form of essays to see the effect of inquiry laerning model of critical thinking ability of students. The hypothesis in this research is examinated by t-test, because the data is distributed normally and it has homogenen variation. Based on the research, the result showed that critical thinkingability t arithmetic > t table (4,23 > 1,67). Therefore, the hypothesis is accepted it can be concluded than applying inquiry learning model can give positive effecttowards students competence of critical thinking ability about excretion system in VIII class SMPN 11 Padang.